Hematological Indices of Sickle Cell Anaemia Patients with Pulmonary Tuberculosis in Northern Nigeria. - Sagir G. Ahmed; Audu A. Bukar; Bashir Jolayemi (Mediterranean Journal of Hematology and Infectious Diseases)
Nigeria has the fourth highest prevalence of TB and the highest prevalence of Sickle cell anaemia (SCA) in the world. SCA patients have impaired immunity and are vulnerable to TB. Hence, we studied the haematological indices of SCA patients with TB in Nigeria. A total of 23 SCA patients with TB were studied in parallel with equal number of age and sex matched SCA patients without TB. SCA patients with TB had significantly lower haematocrit, higher level of circulating sickle cells (CSCs) and similar level of reticulocyte count in comparison to patients without TB. SCA patients with TB had significantly higher mean WBC count associated with higher frequency of neutrophilia in comparison to those without TB. Monocytosis and eosinopenia were exclusively found in SCA patients with TB at frequencies of 52% and 65% respectively. Lymphocyte and basophil counts were normal in all patients with and without TB. Mean platelet counts were high in both patient groups but the frequency of thrombocytosis was significantly higher in patients with TB. SCA patients with TB had significantly higher mean ESR than their counterparts without the infection. The findings of this study  revealed that TB in SCA patients was associated with rising level of CSCs, falling level of haematocrit, sub-optimal reticulocytosis, neutrophilia, monocytosis, thrombocytosis, eosinopenia and rising level of ESR. Hence, SCA patients presenting with these haematological indices should be investigated for TB.